A Case Study of a 15-Minute City Concept in Singapore’s 2040 Land Transport Master Plan: 20-Minute Towns and a 45-Minute City (Unijourn Publisher, 2022)
The 15-Minute city concept emerged as a response to the hyper-motorized city. First popularized by the Mayor of Paris in 2020, 15-Minute City is an evolving concept that derived from its predecessors such as neighborhood-unit planning and walkable city. This paper explores the implementation of the 15-Minute City concept in city planning by using Singapore as the case study. In 2018, Singapore released its Land Transport Master Plan 2040 and which includes an ambitious concept of 20-Minute Towns and a 45-Minute City (2MT45MC) and has similar ideas to the 15-Minute City concept. Through various journal articles and media coverage, Singapore’s policy and regulation regarding its transport planning were thoroughly reviewed to find Singapore’s strategy and challenges in realizing the objective of its 2MT45MC concept. Normalizing active mobility and enhancing connectivity nationwide are the main strategies to overcome the biggest challenges faced: lack of legal backing in personal mobility devices and the country’s rigid zoning. Even though it is too early to say whether 2MT45MC is achievable or not, projects such as the North-South Corridor show that for a long-term plan, it seems feasible.